ICT access and the Nigerian teacher: a literature review - Uyouko, Arit Uyouko; Wong, Su Luan; Mohd Ayub, Ahmad Fauzi (IDOSI Publications, 2014)
Nigeria’s National Policy on ICT’s main objective is to create a conducive environment for rapid expansion of ICT networks and services that are accessible to all at reasonable costs while its policy statement is to ensure the country’s effective participation in regional and international ICT to promote ICT development. Given the emphasis on ICT by the Nigerian government in schools, this study seeks to examine related literature on the state of ICT access currently available to teachers for teaching and learning where focus is given to the Nigerian context.